STUDI PERSEPSI DAN SIKAP MASYARAKAT TENTANG MANFAAT TERUMBU KARANG PADA ZONA INTERTIDAL DI DESA SIDANGOLI GAM KECAMATAN JAILOLO SELATAN KABUPATEN HALMAHERA BARAT - Sinyo, Yumima (Green Earth, 2012)
Perception is a process of giving meaning to the environment. In this case, the objects of perception include interpretations, the input of stimulus, the organization of the stimulus, and the interpretation of the stimulus that has been organized by influencing the behavior and attitude formation.Â This study aims to find out how much the public perceptions and attitude toward the benefits of coral reef at Sidangoli Gam Village, Jaiololo District South West Halmahera. The research was conducted on 6-7 December 2011. It was a survey method and using the questionnaires. Data retrieval is conducted by the public perception questionnaire which is distributed to the respondent. The results showed that the perceptions and attitudes towardÂ the benefits of diversity of coral reefs in the intertidal zone in the Gam Sidangoli Village, Â Jaiololo District South West Halmahera classified as very high. It can be seen from the results of data analysis that the head of the family X> M + 1, 5 (1.82) = 106.98, or 5942.75> 106.98. Key words: Perception, Attitudes, Benefits, coral reefs, Intertidal Zone